2022
DOI: 10.1016/j.bioactmat.2021.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Potential bioactive coating system for high-performance absorbable magnesium bone implants

Abstract: Magnesium alloys are considered the most suitable absorbable metals for bone fracture fixation implants. The main challenge in absorbable magnesium alloys is their high corrosion/degradation rate that needs to be controlled. Various coatings have been applied to magnesium alloys to slow down their corrosion rates to match their corrosion rate to the regeneration rate of the bone fracture. In this review, a bioactive coating is proposed to slow down the corrosion rate of magnesium alloys and accelerate the bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 302 publications
1
29
0
Order By: Relevance
“…Multiple studies have found that macroporous pores in the range of 150 to 360 µm are ideal [40]. This is motivated by the effect of the specific surface area, which is offset in larger pores by the increased potential for cell migration [7,[40][41][42]. The oval-shaped pores with a diameter of 200 to 400 µm affect not only the function of osteoblasts but also chondrogenic differentiation [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have found that macroporous pores in the range of 150 to 360 µm are ideal [40]. This is motivated by the effect of the specific surface area, which is offset in larger pores by the increased potential for cell migration [7,[40][41][42]. The oval-shaped pores with a diameter of 200 to 400 µm affect not only the function of osteoblasts but also chondrogenic differentiation [43].…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradable or bioresorbable implants are the new trend in implantology. Iron-, zinc-, and magnesium-based materials have received a lot of attention [6][7][8]. A significant aspect in implantology is the concept of biocompatibility, understood as the absence of toxic or unfavorable immunological reactions when implants are in contact with cells or bodily fluids [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the last few decades, researchers have put continuous efforts into synchronizing the degradation rate of Mg-based biodegradable implants. Unfortunately, investigated studies show compromised bio-functionalities during clinical testing, which need to be addressed for full-scale orthopedic implant applications [ [6] , [7] , [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of tasks related to the field of biomedical materials science includes the unresolved problem of effective implant osseointegration [1][2][3][4][5][6][7][8]. Currently known materials which can potentially be used as bone allografts have a number of disadvantages, such as reduced biocompatibility, allergic and toxic reactions [9][10][11][12][13][14][15][16][17][18][19][20]. This suggests that the creation of new non-toxic materials that combines high osteointegration and strength characteristics is an urgent task.…”
Section: Introductionmentioning
confidence: 99%